DISTRIBUTION ACCURACY EVALUATION OF RASKIN IN BANGUNTAPAN SUBDISTRICT OF BANTUL DISTRICT - Dwi Utari Indah Nurhandayani; Masyhuri Masyhuri; Dwidjono Hadi Darwanto (Agro Ekonomi, 2013)
This research aims to find out accuracy of the largest distribution, timing quantity, price, administration and quality of Raskin in Banguntapan and find out how much assistance Raskin can meet the needs of the average rice Household Target (Rumah Tangga Sasaran/RTS) in Banguntapan. Methods used is a descriptive analysis by interviewing 50 recipients of Raskin were selected  by random sampling. The data was tested by T test. The result showed that the accuracy rate of the distribution of Raskin in Banguntapan from indicators of accuracy that have been defined in the general guidelines do not meer the  6 indicator accuracy. Only four indicators that can filled which targeted by poverty line of BPS, right price at the distribution point, right at time and right at administration. To be targeted by the poverty line belongs Sayogyo inappropriate because the amount of spending per capita equal to rice in each target houeholds very widely. Data comparison between the number of poor households and the number of Raskin recipients is known that the number of recipients more than the number of households  in Banguntapan, so its not on target. The purchase price of Raskin at the point of distribution in accordance with the conditions set by Bulog. But in this research redeemed price to the point there is a difference in price of about Rp 100/kg to 200/kg that used to transport costs from one place to another. Amount of Raskin that received by each RTS amounted to an average of 9.22 kg and the Raskin are normal qualified. Raskin received by RTS only able to meet the needs of domestic rice consumption amounted to 51.22% per month.